Airflow obstruction was associated with elevation of brachial-ankle pulse wave velocity but not ankle-brachial index in aged patients with chronic obstructive pulmonary disease. Issue 1 (September 2015) - Chen, Rui; He, Wanbing; Zhang, Kun; Zheng, Houzhen; Lin, Lin; Nie, Ruqiong; Wang, Jingfeng; Huang, Hui
Abstract: Objective: Both brachial-ankle pulse wave velocity (baPWV) and ankle-brachial index (ABI) are important predictors for cardiovascular disease (CVD). Patients with chronic obstructive pulmonary disease (COPD) are at high risk of CVD. But the association between airflow obstruction and baPWV or ABI was still unclear. The study was aimed to investigate the influencing factors on arterial stiffness in aged COPD patients. Methods: 67 aged patients with COPD and 67 age- and sex-matched controls without COPD were enrolled in this study. COPD patients were grouped into four groups according to the Global Initiative for Chronic Obstructive Lung Disease Guidelines (GOLD). Both baPWV and ABI were evaluated. Spirometry indices, blood pressure, smoking history and related laboratory parameters were also collected. Results: Comparing with controls, all COPD patients had significantly higher baPWV (1933 ± 355 cm/s versus 1515 ± 256 cm/s, P < 0.001) but not ABI ( P = 0.196). And baPWV values were significantly highest at GOLD stage 4. Forced expiratory volume in 1 s (FEV1 ) was the most significant factor influencing baPWV, after adjusting for age, systolic blood pressure and other traditional cardiovascular risk factors ( β = −0.463, P = 0.014). Conclusion: Arterial stiffness was serious in aged patients with COPD. Spirometry index FEV1 was a possible important predictor for the severity of arterial stiffness of COPD patients. Highlights: Aged COPD patients had higher baPWV but not ABI than age- and sex-matched subjects. Among the four GOLD stages, baPWV values were highest at GOLD stage 4. FEV1 was an important factor affecting baPWV in COPD patients. It helped physicians to be aware of high-risk COPD patients and conduct positive treatment.